Chromium oxide loaded silica aerogels: novel visible light photocatalytic materials for environmental remediation - Weerasinghe, T. Manindu N.; Klabunde, Kenneth J. (My University, 2013)
Various photocatalytic systems have been reported for degradation of harmful air pollutants. Most of the reported catalysts are based on well-known semiconducting material, Titanium Dioxide (TiO[subscript 2]), while some are based on other materials such as Silicon Dioxide (SiO[subscript 2]), various Zeolites. However, titania based systems are very popular in this regard and the most of the photocatalytic processes that involve titania are considered non-localized. Thus, to study the photocatalytic ability of a localized system, novel aerogel based samples were studied using silica and chromium and tested for photocatalytic activities. The new photocatalytic systems were prepared to obtain aerogel silica as the matrix material by cohydrolyzing silica precursor with chromium(III) ions to obtain chromium loaded silica materials. Later, these prepared samples were compared to chromium loaded titania and mixed silica-titania systems. All the prepared systems have high surface areas compared to the systems that have been reported in literature. Samples were characterized by X-ray diffraction, Diffusive reflectance UV spectroscopy, and BET surface analysis methods. The kinetics of photocatalytic degradation of a model pollutant, acetaldehyde, was performed using a Shimadzu GCMS-QP 5000 instrument and a glass reactor with a quartz window. Change in photocatalytic activity was found with various molar ratios of SiO[subscript 2] to TiO[subscript 2]. From all the systems, chromium loaded pure SiO[subscript 2] showed the highest activity towards acetaldehyde degradation compared to mixed systems and TiO[subscript 2] based systems. The interesting photocatalytic activity of silica based materials occurs due to the efficient insertion of chromium ions into silica matrix to generate reactive sites. The photo excitation is believed to occur at molecular orbital level at localized chromium sites.
Keywords: Photocatalysis; Aero gel; Semiconductors; Silicon dioxide; Kinetics; Transition metal incorporation; UV and Visible light